Peran Organisasi Sayap Partai Politik dalam Kaderisasi Partai Politik di Indonesia - Septi Nur Wijayanti; Kelik Iswandi (Faculty of Law, Universitas Pattimura, 2021)
The political parties that emerge in Indonesia have a distinct catch-all character; they are dependent on individual figures and lack a defined socioeconomic foundation. For political parties, the regeneration process has become a struggle. Because certain political parties lack a clear regeneration system, oligarchic recruiting is a common occurrence. Religious affiliations, local links, local commonalities, and proximity to political party leaders all have a role in recruitment trends. This research aims to explain the role of the under bow of the political party on regeneration. This is a legal-normative study that relies on secondary data. The research material is divided into three categories: primary, secondary, and tertiary. The following factors, according to this study, influence political party regeneration and recruitment: 1) political dynasty has an impact on unhealthy regeneration; 2) political dowry has an impact on unhealthy competition among political party members; and 3) popularity factor has an impact on how quickly people can become political party members. Political parties' inability to recruit and regenerate has an impact on their capacity to fulfill their role as the primary source of national leadership selection. Alternative solutions to these problems include strengthening the under bow of political parties. The existence of under bow of political parties will aid in the transmission of political party doctrine. Political parties will be rewarded with the best members who will fight for their vision and goals. Furthermore, the under bow of political parties can serve as educational institutions for potential members before they join the party.